The policing of social discontent and the construction of the social body: mapping the expansion and militerization of the police organization in Turkey in the post-1980 period - Berksoy, Biriz Gonca. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The police organization in Turkey has gone through a major transformation process after the 1980 coup d’état. Within this period its personnel and budget were significantly enlarged, para-militaristic units were established, police powers were extended etc. The thesis examines the expansion and militarization of the police organization in Turkey in the post-1980 period. As the thesis puts forward, this process can neither be evaluated as a “modernization” move to advance the public “services”; nor as an isolated case caused by the particular “anti-democratic” methods of the state in Turkey. The grounds of this transformation, whose equivalents had been experienced previously in the bedrocks of neo-liberalism (United States and Britain), must be sought within the legacy of social relations in the country and in the path-dependent neoliberalization process, through which this legacy have been re-constructed since the beginning of 1980s. This is accomplished in the thesis by taking into account four clusters of social relations and their re-configuration since 1945, for it is claimed that they constitute the minimum core relations that comprise the capitalist state and their modifications leave a major impact upon its institutions, especially if it is a police organization. These are the relations constituting the accumulation regime, hegemonic discursive relations, relations between state institutions affecting the iv political regime and international relations leading to international norm/policy transfers.
Keywords: Police -- Turkey -- History.